The Convergence of Onomatope Animal Sounds between Indonesian And English - Ruli Hapsari (Ahmad Dahlan Journal of English Studies, 2017)
This qualitative study is aimed at discovering the similarities of onomatope (not onomatopoeia) animal sounds between two unrelated languages, Indonesian and English. The investigation operates on phonological system with some goals to achieve; to describe how sounds of onomatope animal correspond, to explain why the two languages share similarities in their onomatope animal sounds. Â The data in this research are from Indonesian and English comics which are backed up by interviews with twenty-six informants consisting of eleven adults and fifteen children. The interviews are aimed at reinforcing the collected data and also disqualifying several lingual units which under suspicion of loan sound imitations.The research findings reveal that out of 22 (twenty-two) onomatope animal sounds gathered as the research data, there are only 15 (fifteen) sharing the same phoneme distribution after conducting sound correspondence. The phoneme distribution occurs mostly on onset position, the second is on coda position, and the least is on nucleus position. There are three factors which evoke the similarities or that can be called convergence. First, because of similarities in phoneme inventories. Second, because of similarities in phonotactic rules. Third, because of same sound symbolism which apply to both Indonesian and English.Â